ADOPTION OF MOBILE PHONE USE BY SHEA BUTTER PROCESSORS - Iddrisu, B; Al-hassan, S (UDS International Journal of Development, 2016)
This paper analyses the effects of the use of mobile phones on shea butter women micro enterprise growth in Northern Region of Ghana. A total of 200 women shea butter processors were selected from two districts (Sagnarigu and Kumbungu Districts) through multi-stage sampling technique. Data was gathered through semi-structured interviews and focus group discussions. The Pearson’s Chi square results indicated that age, marital status and education have significant effects on mobile phone use. The student t test results showed a positive and significant relationship between mobile phone use and enterprise growth in terms of income and output. Network Failure (92%), high airtime charges (60%) and illiteracy (88%) were found to be the three major challenges affecting the use of mobile phones in the shea butter micro enterprise in Ghana. It is recommended that training should be organized for the shea butter processing women on key areas such as mobile phone use and handling of phones. This will enable them to access up-to-date information on shea butter production and marketing. Mobile phone providers should improve upon their services and also come out with various ways of making the airtime affordable for the women shea processors. Keywords: Mobile phone, Shea butter, Adoption, Service providers